Chicago Discussions -Discussion of paper of Prof. ?kerman (See p. 265). (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1894)
Joseph HartshoRnE, Pottstown, Pa.: I have read Professor Akerman's valuable paper with great interest. Few of the present generation of American steel metallurgists are aware of the very important part taken by Swedish engineers in the successful development of the Bessemer proeess, and I am afraid some of the older ones have forgotten it. Certainly, I think, most of us would have said that Terre Noire was the first to introduce the use of metal direct from the blast-furnace. It is very well, therefore, that honor should be given to whom honor is due. I can speak from personal experience upon one part only of Prof. Akerman's paper; namely, the effect of the temperature at which the molten metal is cast upon the quality of the finished steel. In a general way I have, of course, known for a long time that the